Minat Dan Hasil Belajar Mahasiswa Prodi Pendidikan Biologi Universitas Muhammadiyah Surabaya Dalam Penerapan Metode Bermain Peran (Role Playing) Pada Perkuliahan Biokimia Materi Sintesis Protein - Malihatul Fadliyah (Universitas Muhammadiyah Surabaya, 2017)
Abstract: This study aims: 1). To know the interest of students studying in biology education program of University of Muhammadiyah Surabaya, with the application of role play method (Role Playing) on lecturing biochemistry of protein synthesis material, 2). To know the study resultof students in biology education of University of Muhammadiyah Surabaya with the application of role playing method (Role Playing) on lecture biochemistry of protein synthesis material, 3). To know the response of student of biology education program of University of Muhammadiyah Surabaya with the application of role play method (Role Playing) on lecture biochemistry of protein synthesis material. This study is a Pre-experimental study with One Pretest-Postest group design. The research sample is student in class 2015 periode. Technique of collecting data using observation method, test and questionnaire. Technical analysis of data used descriptive and statistical analysis. The result of the percentage of interest in learning data at the first meeting (before being given role playing method) is 81.66% and the second meeting (after being given role playing method) is 90.45%. The result of statistical test of difference of mean using paired t-test at Î± = 0,05, note that significance value (p) = 0,00 because p value <0,05. The cognitive learning outcomes of the students after being given the role-playing method were significantly higher than before they were given role playing method with pretest average of 40 and posttest of 78.6. Questionnaire student response included in high category that is equal to 98,43%. The conclusion of this research is the application of role playing method to increase student's interest and learning result.Â